2021
DOI: 10.1002/chem.202101700
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Deintercalation From the Spinel‐Type MgMn2‐yFeyO4 (0.4≤y≤2.0) by Acid‐Treatment and Electrochemistry

Abstract: Rechargeable magnesium batteries attract lots of attention because of their high safety and low cost compared to lithium batteries, and it is needed to develop more efficient electrode materials. Although MgMn 2 O 4 is a promising material for the positive electrode in Mg rechargeable batteries, it usually exhibits poor cyclability. To improve the electrochemical behavior, we have prepared nanoparticles of MgMn 2-y Fe y O 4 . The XRD results have confirmed that when Mn 3 + (Jahn-Teller ion) ions are replaced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…According to previous theoretical studies, 44 , 46 Mg deinsertion and insertion with redox of Mn 3+ /Mn 4+ can occur around 2.8 V vs Mg/Mg 2+ in the case of MgMn 2 O 4 . As for the acid-treated MgMn 2 O 4 (demagnesiated Mg x Mn 2 O 4 ), 20 it was also suggested that a pseudoplateau due to the oxidation up to Mn 4+ was observed at ca. 2.5 V vs Mg/Mg 2+ .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…According to previous theoretical studies, 44 , 46 Mg deinsertion and insertion with redox of Mn 3+ /Mn 4+ can occur around 2.8 V vs Mg/Mg 2+ in the case of MgMn 2 O 4 . As for the acid-treated MgMn 2 O 4 (demagnesiated Mg x Mn 2 O 4 ), 20 it was also suggested that a pseudoplateau due to the oxidation up to Mn 4+ was observed at ca. 2.5 V vs Mg/Mg 2+ .…”
Section: Resultsmentioning
confidence: 96%
“…As can be seen in Figure 3 , the averaged structure could be refined under these hypotheses, and thus it is demonstrated that Mg and Mn exist basically at the tetrahedral and octahedral sites, respectively, as reported previously. 20 , 44 Distortions of the tetrahedra ( M O 4 ) and octahedra ( M O 6 ) were calculated from the refined structural parameters. Table 3 summarizes the polyhedral volumes, quadratic elongations (λ), and bond-angle variances (σ 2 ), which are indices of the polyhedral distortions.…”
Section: Resultsmentioning
confidence: 99%
“…A way to overcome this could be the partial replacement of Mn by other elements. Thus, the partial substitution of Mn by iron has been explored to increase the stability of MgMn 2-y Fe y O 4 during the electrochemical cycling [ 38 , 39 ]. The Jahn–Teller distortion of the structure can be suppressed by incorporating iron to the spinel and the structure becomes cubic (s.g. Fd m).…”
Section: High-voltage Electrodementioning
confidence: 99%
“…The maximum reversible capacity usually observed for these materials is about 130 mAh g −1 [ 39 ], although the maximum theoretical capacity is 616 mAh g −1 (referred to MnO 2 , and Mg content up to Mg 2 Mn 2 O 4 ). Kobayashi et al raised the experimental capacity of MgMn 2 O 4 up to 230 mAh g −1 by using cubic particles with ca.…”
Section: High-voltage Electrodementioning
confidence: 99%
See 1 more Smart Citation